Cyclopropenes: a new tool for the study of biological systems. Issue 6 (27th March 2017) - Ravasco, João M. J. M.; Monteiro, Carlos M.; Trindade, Alexandre F.
Abstract : Cyclopropenes have become an important mini-tag tool in chemical biology, participating in fast inverse electron demand Diels–Alder and photoclick reactions in biological settings. Abstract : The development of novel bioorthogonal reagents for biological applications has increased considerably in the last decade. Of these tools, the modification of biological entities by metabolic labelling strategies employing chemical mini-tags has allowed the study of these entities within biological samples. Following this strategy, apart from azides, cyclopropene units have recently emerged as potential alternative mini-tags that react quickly in tetrazine and photoclick ligation reactions. Herein the most recent advances in bioorthogonal chemistry, covering the synthesis, stability and reactivity of cyclopropenes, as well its applications in biological systems, are reviewed.